The evaluation a proposed strategy for the Ministry of Planning for the years 2018-2022 . - الكبيسي صلاح الدين عواد; حميد شيماء محمد (Journal of Economics and Administrative Sciences, 2018)
abstract the research discussed a stage of strategic management. The strategic of the evaluation of the proposed strategy through feedback is to ensure that it is implemented with the least possible variation. The research aims at evaluation a proposed strategy for the Ministry of Planning for the years 2018-2022 in line with the orientations of the state, taking into account the surrounding environmental conditions. It relies on scientific bases and steps to formulate the strategy The extent of the strategy suitability was tested through a set of statistical means and its objectivity was verified through a survey of a number of specialized experts who were selected in accordance with the principle of intentional sampling in order to select the experts most compatible with the strategy. The questionnaire was used to survey the experts’ opinions(15) as beneficiaries of the strategy proposed to the Ministry, on whom the follow-up of its execution fell, as well as the opinions that the researcher drew during the interviews with many of the executive managers as being closer to the implementation process and with direct contact. The results indicated a clear acceptance of the strategy and in line with the strategic alternative proposed to the ministry, especially that they included the obstacles, time horizon, strategic issues, programs and procedures, the determination of the implementation entity, follow-up and the definition of evaluation criteria. A number of recommendations were presented, most notably the need to adopt this proposed strategic document, especially as it reflects the Ministry reality and responds to the requirements of its developmental role.